Evaluating the integration of seaport container terminals in supply chains - Song, Dongwook; Panayides, Photis (My University, 2008)
Purpose - The purpose of this paper is to define and empirically develop measures to evaluate the extent of integration of seaport container terminals in supply chains. Design/methodology/approach - A literature review identified four key variables hypothesized to be part of the higher-order construct of "terminal supply chain integration (TESCI)". The hypotheses were theoretically justified a priori and data for operationalizing the conceptualized variables obtained via a large-scale survey of container terminal operators. A model was developed and validated using confirmatory factor analysis. Findings - The validated variables of the higher-order construct of TESCI included "information and communication systems", "value-added services", "multimodal systems and operations" and "supply chain integration practices". Research limitations/implications - The study develops measures from the standpoint of the container terminal (the centric supply chain actor). Supply chains involve a network of companies and it would be useful to obtain data as to integration from other supply chain participants. The usual caveats of cross-sectional research apply and longitudinal case studies may provide supplementary information. Practical implications - There are valuable practical implications for container terminals that seek to measure the extent of integration into supply chains and for port users that place value on container TESCI in their choice and evaluation criteria. Originality/value - The study is the first of its nature that attempts to provide a valid theoretical construct and empirical measures of seaport container TESCI. The study shifts container TESCI from an abstract concept to a theoretical construct with validated measures
Keywords: Logistics--Management; Harbors; Containers; Docks; Business logistics